To solve the equation \( 3 - \frac{6}{5}x = -3 \), follow these steps:
- First, isolate the term containing \( x \). Subtract 3 from both sides of the equation:
\[
- \frac{6}{5}x = -3 - 3 \]
\[
- \frac{6}{5}x = -6 \]
- Next, to eliminate the negative sign, multiply both sides by -1:
\[ \frac{6}{5}x = 6 \]
- Now, to solve for \( x \), multiply both sides by the reciprocal of \( \frac{6}{5} \), which is \( \frac{5}{6} \):
\[ x = 6 \cdot \frac{5}{6} \]
- Simplifying the right side:
\[ x = 5 \]
Thus, the solution is \( x = 5 \).